Penilaian Persepsi Masyarakat Terhadap Bangunan Besejarah Di Koridor Kayutangan, Malang, Indonesia - Azis, Baskoro; Santosa, Herry; Ernawati, Jenny (University of Merdeka Malang, 2019)
Malang is well-known for colonial buildings. Visual quality of historic buildings in the Kayutangan corridor makes it an icon of Malang City. Assessment of visual quality is affected by daytime conditions. Day lighting are factors that influenced the visual quality assessment of historic buildings. This study meant to assess the visual quality of historic buildings and aspects that influence by society during the day. This study used a descriptive quantitative method explaining public perception about the visual quality of historical buildings in Kayutangan street corridors during the day. Semantic Differential Scale (SD) was the instrument to describe the respondents’ perceptions (positive and negative ones). From the result showed that visual quality of 1 of 10 historic buildings in Kayutangan was below the average scores and the most influential variables by society with day lighting in the historic building.DOI: https://doi.org/10.26905/lw.v11i1.2514